Sufi Interpretation: A Fundamental Difference from Philosophical Interpretation - Abdul Aziz; Muhammad Arif (al-Afkar, Journal For Islamic Studies, 2025)
This paper aims to reveal the fundamental differences between tafsir Sufi and tafsir falsafi, focusing on the explanation of tafsir Sufi. The method used in this research is qualitative by using an analytical-descriptive approach through literature study. The results of the discussion of this paper include Sufi interpretation in terms of understanding, then the history surrounding the emergence of Sufi interpretation, where many of its movements were detected after the death of the Prophet, then the limits of Sufi interpretation and differences of opinion in its acceptance accompanied by their respective arguments. In the end, it is necessary to distinguish between Sufi interpretation and falsafi interpretation which is allegedly in contact with one another.